2023
DOI: 10.1038/s41419-023-05555-z
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-derived LRIG3 interacts with NETO2 in tumor-associated macrophages to modulate microenvironment and suppress tumor growth

Abstract: Tumor-associated macrophages (TAMs) account for 30–50% of glioma microenvironment. The interaction between glioma tumor cells and TAMs can promote tumor progression, but the intrinsic mechanisms remain unclear. Herein, we reported that soluble LRIG3 (sLRIG3) derived from glioma tumor cells can block the M2 polarization of TAMs via interacting with NETO2, thus suppressing GBM malignant progression. The expression or activity of ADAM17 in glioma cells was positively correlated with the expression of sLRIG3 in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Although we have demonstrated that CD58 and sCD58 activate AKT signaling pathway, it is not clear how sCD58 increases the phosphorylation level of AKT. Interestingly, LRIG3 and sLRIG3 can regulate the MET/PI3K/Akt pathway in GBM [ 42 ], and further study found sLRIG3 also binds to the transmembrane protein NETO2 to activate the NF-kB pathway in GBM [ 43 ]. TELO2, a cofactor of phosphatidylinositol 3-kinase-related kinases, has been reported to bind to RICTOR as the mTORC2 complex and promote CRC cell progression through the AKT pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we have demonstrated that CD58 and sCD58 activate AKT signaling pathway, it is not clear how sCD58 increases the phosphorylation level of AKT. Interestingly, LRIG3 and sLRIG3 can regulate the MET/PI3K/Akt pathway in GBM [ 42 ], and further study found sLRIG3 also binds to the transmembrane protein NETO2 to activate the NF-kB pathway in GBM [ 43 ]. TELO2, a cofactor of phosphatidylinositol 3-kinase-related kinases, has been reported to bind to RICTOR as the mTORC2 complex and promote CRC cell progression through the AKT pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To directly observe tumor growth, 150 mg/kg d -Luciferin (Shanghai Yuanye) was injected intraperitoneally into anesthetized mice, and tumor growth images were acquired by an in vivo imaging system (IVIS) after 5 min. All mice were imaged in second week and weekly measured until the first mouse developed neurological symptoms, then killed when neurological symptoms occurred 12 , 13 .…”
Section: Methodsmentioning
confidence: 99%